Intregrasi Nilai-Nilai Pancasila Dalam Fatwa Fatwa Majelis Ulama Indonesia Terkait Hukum Islam - Ahmad Muhammad Musain Nasoha; Asgfiya Nur Atqiya; Aishka Prita Fitriani; Eriza Fitria Novika; Tiara Anggi Sholihah (Amandemen: Jurnal Ilmu pertahanan, Politik dan Hukum Indonesia, 2025)
This research examines the integration of Pancasila values ​​in fatwas issued by the Indonesian Ulema Council (MUI) regarding Islamic law, with the aim of understanding how the country's basic principles are accommodated in religious decisions that have a broad influence on society. Considering that the MUI plays a significant role in providing legal and moral guidance for Muslims in Indonesia, the fatwas it issues not only reflect an understanding of Islamic law, but must also be in line with the normative framework of Pancasila. This research uses a qualitative approach with analysis of the texts of fatwas issued by the MUI in the last five years, as well as in-depth interviews with experts in Islamic law and Pancasila. The research results show that, although the MUI attempts to integrate Pancasila values, there are several challenges in implementing these values, especially related to issues involving religious pluralism, human rights and social justice. The integration of Pancasila in the MUI fatwa is not only important to maintain social harmony amidst Indonesia's diversity, but also to ensure that the application of Islamic law can contribute to inclusive and just national development. Therefore, the MUI is faced with the crucial task of continuing to develop a more contextual and inclusive approach in formulating fatwas, so that it not only fulfills the demands of sharia, but also supports the nation's ideals as mandated by Pancasila.